Characterizing pearlite transformation in an API X60 pipeline steel through phase-field modeling and experimental validation - Araghi, Mohammad Y.; Parsa, M. H.; Ghane Ezabadi, Mostafa; Roumina, Reza; Mirzadeh, Hamed; Xu, Shuozhi (Frontiers in Materials, 2024)
This study explores the microstructural characterization of the pearlite phase transformation in the High Strength Low Alloy API X60 steel, which is used in pipelines. Understanding the formation, phases percentages, and morphology of the pearlitic phase is crucial since it affects the mechanical properties of the considered steel. In this research a phase field model, particularly the Cahn-Hilliard approach, was used in order to simulate the formation and the morphology of pearlite phase in response to different heat treatments. Both double and triple-well potentials were considered for comprehensively studying pearlite's morphology in the simulations. The simulation results were then compared with experimental outcomes obtained by the metallography and field emission scanning electron microscopy analyses. Considering a double-well potential can help to simulate only two-phases, ferrite and cementite, which is less compatibile with the experiment results than the triple-well potential, which gives possibility of simulating a three phase microstructure, ferrite, cementite and austenite and a better match with experimental data. The study reveals that as the cooling rate increases, the interlamellar spacing and layer thickness decreases. Additionally, the difference between experimental and simulation results using triple-well potential was about ~10%. Therefore, the triple-well potential formulation predictions have better agreements with the experimental results for the development circumstance of the pearlitic structures.